What are they saying? A speech act analysis of a vaccination information debate on Facebook - Bonnici, Laurie; Ma, Jinxuan (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2021)
The global resurgence of vaccine preventable diseases is garnering attention amid the COVID-19 pandemic. Vaccination information debates in a Facebook group give participants access to second-hand knowledge conveying personal experiences. Through the lens of Speech Act Theory, this study analysed discourses on pro-and anti-vaccination perspectives along with views from vaccine hesitant groups. Analysis reveals significant criticism of behaviour around information. Findings indicate provision of substantiating information would play a crucial role in debate within divergent information contexts. Application of Speech Act Theory serves to inform participant communication more intimately and empowers their engagement in polarized discussion.